CYTOMEGALOVIRAL INFECTION (Лучшие интеллектуальные исследования, 2025)
Cytomegaloviral infection is a wide-spread human infection with different mechanisms of transmission. A variety of clinical manifestations of the disease is determined by the ability of the human cytomegalovirus to infect nearly all the body cells. Cytomegalovirus may affect immunodeficient individuals, which has resulted in an ongoing increase in cytomegaloviral infection incidence not only among the pediatric, but also among the adult population. According to the European regional bureau of World Health Organization, cytomegaly is classified as a "new and mysterious" infection. A clinical experience case specifies a possibility of disease development in primarily immunocompetent people.